Deteksi Bakteri Endofit Dan Pengaruh Microbacterium arborescens Terhadap Pertumbuhan Sorgum Manis (Sorghum bicolor) - Putri, Riana Nindita (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
This research aims to detect the presence of potential endophytic bacteria, one of which is Microbacterium arborescens and study the effects on the growth of local variants of sweet sorghum plants from farmers in Sleman, Yogyakarta. This research began with infection of Microbacterium arborescens bacteria on sorghum seeds. Sorghum plants were grown in sterile media for 14 days after germination to observe seven growth parameters, including root length, number of lateral roots, stem length, number of leaves, leaf length, wet weight, and dry weight. Analysis of sweet sorghum growth parameters based on the one way ANOVA statistical test. Samples of infected and uninfected sorghum plants in the roots, stems, and leaves were amplified for the 16s rRNA gene using Bioline PCR hotstart mix. The primers used are universal primer Primer 27 f (59-AGA GTT TGA TCM TGG CTC AG-39) and 1492 r (59- TAC GGH TAC CTT GTT ACG ACT T-39). The root length and number of lateral roots between sweet sorghum with and without Microbacterium arborescens infection showed significant differences. The length of the control roots was 9.24 cm, the treatment plants were 6.38 cm, the control plants had six treatment roots, and the treatment plants had ten lateral roots.